The concept of peri-operative medicine to prevent major adverse events and improve outcome in surgical patients: A narrative review. Issue 12 (December 2019) - Bollen Pinto, Bernardo; Chew, Michelle; Lurati Buse, Giovanna; Walder, Bernhard
Abstract : N/A: Peri-operative Medicine is the patient-centred and value-based multidisciplinary peri-operative care of surgical patients. Peri-operative stress, that is the collective response to stimuli occurring before, during and after surgery, is, together with pre-existing comorbidities, the pathophysiological basis of major adverse events. The ultimate goal of Peri-operative Medicine is to promote high quality recovery after surgery. Clinical scores and/or biomarkers should be used to identify patients at high risk of developing major adverse events throughout the peri-operative period. Allocation of high-risk patients to specific care pathways with peri-operative organ protection, close surveillance and specific early interventions is likely to improve patient-relevant outcomes, such as disability, health-related quality of life and mortality.